MAKNA PERSELINGKUHAN SEBAGAI PRISTIWA YANG MENGUBAH BATAS PRIVASI KOMUNIKASI KORBAN DALAM HUBUNGAN PERNIKAHAN: PERSPEKTIF COMMUNICATION PRIVACY MANAGEMENT - Elsa Nikita; Ririn Puspita Tutiasri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Infidelity in marriage not only affects interpersonal relationships between spouses but also influences how victims manage personal information following the betrayal. This study aims to analyze the communication privacy management of infidelity victims in marital relationships using Sandra Petronio's Communication Privacy Management Theory. This research employed a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with eight informants who had experienced infidelity in their marriages. The findings reveal that victims establish privacy boundaries by considering whether to disclose or conceal information about the infidelity, selectively choosing trusted individuals to receive such information, managing privacy boundaries on social media, negotiating information ownership with family members and close friends, and rebuilding their privacy and personal identity after the betrayal. The study also found that the management of communication privacy is dynamic and influenced by emotional conditions, trust, family considerations, and social consequences resulting from information disclosure. This study contributes to communication studies by demonstrating that victims actively negotiate and reconstruct their communication privacy following marital infidelity rather than merely concealing personal information.